2020
DOI: 10.1002/celc.202000926
|View full text |Cite
|
Sign up to set email alerts
|

Seemingly Negligible Amounts of Platinum Nanoparticles Mislead Electrochemical Oxygen Reduction Reaction Pathway on Platinum Single‐Atom Catalysts

Abstract: A few studies have claimed that Pt single‐atom catalysts (SACs) can catalyze the oxygen reduction reaction (ORR) following a four‐electron pathway (O2+4H++4e−→2H2O). Here, we show that, in the presence of a seemingly negligible amount of Pt nanoparticles, the ORR can mistakenly be thought to occur via a four‐electron pathway on Pt SACs. Various weight percentages (1, 2, 4, 8 wt%) of Pt SACs were prepared on C3N4 layers deposited on a carbon support (C@C3N4). Through a combination of H2/CO uptakes and high angl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
(44 reference statements)
0
6
0
Order By: Relevance
“…We showed that if seemingly negligible Pt nanoparticles coexist with Pt single atoms, the ORR reaction pathway can mistakenly be thought to follow a four-electron pathway on Pt SAC. 108 We prepared 1, 2, 4, and 8 wt % Pt supported on a carbon support with thin C 3 N 4 shell (C@C 3 N 4 ). Whereas 1 and 2 wt % Pt/C@C 3 N 4 consisted of Pt single atoms only, the 4 wt % catalyst contained a small amount (∼0.6 wt %) of Pt nanoparticles as well.…”
Section: Overcoming the Limitations Of Typical Sac Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…We showed that if seemingly negligible Pt nanoparticles coexist with Pt single atoms, the ORR reaction pathway can mistakenly be thought to follow a four-electron pathway on Pt SAC. 108 We prepared 1, 2, 4, and 8 wt % Pt supported on a carbon support with thin C 3 N 4 shell (C@C 3 N 4 ). Whereas 1 and 2 wt % Pt/C@C 3 N 4 consisted of Pt single atoms only, the 4 wt % catalyst contained a small amount (∼0.6 wt %) of Pt nanoparticles as well.…”
Section: Overcoming the Limitations Of Typical Sac Structuresmentioning
confidence: 99%
“…However, Pt nanoparticles coexisted with Pt single atoms in these catalysts, and it is unclear whether the four-electron pathway ORR really occurred on the Pt single atoms. We showed that if seemingly negligible Pt nanoparticles coexist with Pt single atoms, the ORR reaction pathway can mistakenly be thought to follow a four-electron pathway on Pt SAC . We prepared 1, 2, 4, and 8 wt % Pt supported on a carbon support with thin C 3 N 4 shell (C@C 3 N 4 ).…”
Section: Overcoming the Limitations Of Typical Sac Structuresmentioning
confidence: 99%
“…The seemingly negligible number of nanoparticles can cause a misinterpretation of the reaction pathway. 20 Chronoamperometry (which measures the current change at a fixed potential for a long time) or chronopotentiometry (which measures the potential change at a fixed current for a long time) is usually used to test the durability of various electrochemical reactions, but these techniques are usually considered to be mild. Cyclic voltammetry (CV, which measures i−V curves repeatedly in a fixed potential range) might be a more reliable method for showing the actual durability.…”
Section: Introductionmentioning
confidence: 99%
“…[ 16 ] However, in recent endeavors to develop atomically dispersed Pt catalysts to maximize noble metal utilization, many have demonstrated a high selectivity toward the 2 e ORR instead, and concluded that isolated Pt single atoms cannot effectively break the O─O bond and therefore exhibit poor selectivity toward the 4 e ORR process due to the absence of Pt–Pt ensemble sites. [ 7,13,17 ]…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, SACs may not be a panacea for all catalytic reactions, especially not for those that require multiple neighboring active atoms to work in tandem. [ 6,7 ] The absence of such ensemble sites in SACs often compromises the activity and/or selectivity toward certain reactions, such as the low‐temperature oxidation of CO, C 3 H 6 , and C 3 H 8 , [ 8,9 ] vinyl acetate synthesis, [ 10 ] selective conversion of acetylene to ethylene, [ 11 ] and ethylene hydrogenation. [ 12 ]…”
Section: Introductionmentioning
confidence: 99%